Bibliometric and visual analysis of human microbiome—breast cancer interactions: current insights and future directions - Zhou, Yi; Jiang, Min; Li, Xiaoyu; Shen, Ke; Zong, Hui; Lv, Qing; Shen, Bairong (Frontiers in Microbiology, 2024)
The composition of the gut microbiome differs from that of healthy individuals and is closely linked to the progression and development of breast cancer. Recent studies have increasingly examined the relationship between microbial communities and breast cancer. This study analyzed the research landscape of microbiome and breast cancer, focusing on 736 qualified publications from the Web of Science Core Collection (WoSCC). Publications in this field are on the rise, with the United States leading in contributions, followed by China and Italy. Despite this strong output, the centrality value of China in this field is comparatively low at ninth, highlighting a gap between the quantity of research and its global impact. This pattern is repetitively observed in institutional contributions, with a predominance of Western institutes among the top contributors, underscoring a potential research quality gap in China. Keyword analysis reveals that research hotspots are focused on the effect of microbiome on breast cancer pathogenesis and tumor metabolism, with risk factors and metabolic pathways being the most interesting areas. Publications point to a shift toward anti-tumor therapies and personalized medicine, with clusters such as “anti-tumor” and “potential regulatory agent” gaining prominence. Additionally, intratumor bacteria studies have emerged as a new area of significant interest, reflecting a new direction in research. The University of Helsinki and Adlercreutz H are influential institutions and researchers in this field. Current trends in microbiome and breast cancer research indicate a significant shift toward therapeutic applications and personalized medicine. Strengthening international collaborations and focusing on research quality is crucial for advancing microbiome and breast cancer research.